Sastra dan Sains: Jalinan Imajinasi dan Logika Serta Dampaknya Bagi Pendidikan, Masyarakat, dan Budaya - Yuentie Sova Puspidalia; Junaidi Junaidi; Ibnu Hasyim (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2025)
This article aims to describe the relevance of the two disciplines in human life and explain that imagination in literature and logic in science are related to each other. To review it, an interdisciplinary conceptual qualitative approach with a literature study design is used in data collection. Furthermore, conceptual analysis (theoretical and theme analysis) and critical narrative analysis, and synthesis were conducted. The results of the discussion show that the integration of literature and science creates a relationship that enriches understanding and new discoveries in both disciplines. Science, which is based on logic, observation and experimentation, allows researchers to explore hypotheses objectively and measurably. The use of the term science shows the close connection between literary imagination and the logic of science. While science focuses on facts and reality, literature is able to explore deeper meanings by utilizing scientific terms, making it more accessible to readers. Imagination and logic are not only the driving force for human civilization, but also help society to adapt to change and develop creativity. Therefore, the development of literature and science involving these two elements is crucial in shaping human insight and knowledge. Nonetheless, the acceptability of science does not escape the constraints of traditional beliefs and culture. This can be addressed through collaboration in improving science literacy and facilitating dialogue between science and culture